2015
DOI: 10.1039/c5cc02321a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of unique six-coordinated titanium species with an organic amine ligand in titanosilicate and their unprecedented high efficiency for alkene epoxidation

Abstract: A novel organic-inorganic layered titanosilicate consisting of Ti-containing MWW-type nanosheets and piperidine ligands was constructed. It exhibited an unprecedented high catalytic activity and recyclability in alkene epoxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 16 publications
5
75
0
1
Order By: Relevance
“…S1, ESI †), and a shoulder peak at 459.6 eV and the main peak at 460.2 eV were detected in TS-1 + as the binding energy of Ti 2p 3/2 , indicating that the charge distribution of the Ti ions in TS-1 + was more negative, which provides the possibility of water ligands coordinating directly to the Ti active sites. 12 The results of IR and XPS in TS-1 + further verify the formation of "TiO 6 " octahedron species proposed by Li et al that it is partially coordinated with water and hydroxyl groups shown as Ti(OSi) 2 (OH) 2 (H 2 O) 2 . 9d The proportion of "TiO 6 " species in TS-1 + remained almost unchanged around 20% in various Ti contents via semiquantitative analysis by UV/Vis measurement (Table S1, ESI †).…”
Section: Synthesis Of Highly Active Oxidation Catalyst With Improved supporting
confidence: 70%
“…S1, ESI †), and a shoulder peak at 459.6 eV and the main peak at 460.2 eV were detected in TS-1 + as the binding energy of Ti 2p 3/2 , indicating that the charge distribution of the Ti ions in TS-1 + was more negative, which provides the possibility of water ligands coordinating directly to the Ti active sites. 12 The results of IR and XPS in TS-1 + further verify the formation of "TiO 6 " octahedron species proposed by Li et al that it is partially coordinated with water and hydroxyl groups shown as Ti(OSi) 2 (OH) 2 (H 2 O) 2 . 9d The proportion of "TiO 6 " species in TS-1 + remained almost unchanged around 20% in various Ti contents via semiquantitative analysis by UV/Vis measurement (Table S1, ESI †).…”
Section: Synthesis Of Highly Active Oxidation Catalyst With Improved supporting
confidence: 70%
“…2-bottom left). The TOF values indicate that the reaction is reasonably fast, in comparison with other non-functionalized titanosilicates, used under similar conditions, for epoxidation of cyclohexene with TBHP [88][89][90][91]. ICP-AES experiments were conducted on samples 1-7 to evaluate the bulk Ti content in the materials (ESI , Table S2).…”
Section: Determining the Factors That Affect Catalytic Activitymentioning
confidence: 99%
“…The catalytic results revealed that the hierarchical LTS-1 was less active than the conventional TS-1 in the epoxidation of 1-hexene with H 2 O 2 (6.5% for LTS-1 and 25.2% for TS-1, respectively), because LTS-1 contained a large number of silanol groups than TS-1. [ 146 ] Further characterizations indicated that the resulting organic-inorganic layered titanosilicate contained unusual six-coordinated Ti active site with an organic PI ligand. However, the conversion of 1-hexene achieved on LTS-1 indicated that its catalytic behavior was still characteristic of crystalline titanosilicate rather than Ti-containing mesoporous materials.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…However, the conversion of 1-hexene achieved on LTS-1 indicated that its catalytic behavior was still characteristic of crystalline titanosilicate rather than Ti-containing mesoporous materials. [ 146 ] Moreover, a family of UTL-type titanosilicates were prepared through the conventional hydrothermal synthesis and the following ADOR process, producing the UTL titanosilicate, Ti-IPC-2, Ti-IPC-4, the silica pillared Ti-IPC-1PISi, and the silica-titania pillared Ti-IPC-1PITi catalysts. Moreover, LTS-1 was immune to Ti leaching and irreversible deactivation in cyclohexene epoxidation with H 2 O 2 compared with the mesoporous Ti-MCM-41, because of the crystalline characteristics of catalyst.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%